ADAPTATION OF THE FIRST FORM PUPILS TO EDUCATIONAL ACTIVITY IN PRIMARY SCHOOL - Микола Прозар (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article presents the results of a study of adaptive possibilities (social and psychological) of pupils of the first form to the educational activities in secondary schools. Using the research methods, an one-year experiment was conducted: the pupils of the first forms of Kamjanets-Podilsky secondary schools  № 13 and № 14 (73 boys and 87 girls) were selected by the method of random sample. The study found that the living conditions of the 6-year-olds (due to the beginning of education in secondary school) do not assist formation of adequate adaptation: at the beginning, the social and psychological adaptation correspond to the average level, and in the end - to the lowest one. Obtained results give reason to conclude that the learning activities in the first year of study negatively affects the adaptive possibilities of the first form pupils; it results in poor mental capacity and health of pupils.